ANALYSIS OF DVI LINE BREAK IN ATLAS TEST FACILITY USING RELAP5 CODE - LE , DAI DIEN; NGUYEN , THI TU OANH (Nuclear Science and Technology, 2011)
The ATLAS (Advanced Thermal-hydraulic Test Loop for Accident Simulation) is an integral effect test for simulating APR1400 reactor in a wide range of accident conditions. Most of the safety injection features of the APR1400 are incorporated into the safety injection system of the ATLAS. It is a half-height and 1/288-volume scaled test facility with respect to the APR1400 included a primary system, a secondary system, a safety injection system, a break simulating system, a containment simulating system, and auxiliary systems. The DVI line break test of the APR1400 was done on ATLAS with the same pressure and temperature conditions and was chosen as the first domestic standard problem of Korean Nuclear Industry. The calculations presented in the paper have been carried out with the RELAP5 code. The calculation was run for the steady state already supplied in DSP-1 and then, the transient calculations for DVI break were performed for the time period of 2000 seconds. The main calculation results are in good agreement with experiment data and results reported by KAERI, KINS and KNF.